Perilaku dan persepsi masyarakat terhadap terjadinya kebakaran gambut di Ogan Komeriling Ilir Provinsi Sumatera Selatan - Ati D Nurhayati; Bambang Hero Saharjo; Leti Sundawati; Syartinillia; Yeni Vetrita (Graduate School Bogor Agricultural University (SPs IPB), 2020)
South Sumatera Province experienced the worst peat fires in 2015, where the larger area is located in Ogan Komering Ilir (OKI) District. Human activity is a very important factor in causing forest and peatland fires,because in fact nearly almost 100 % of forest and land fires are caused by human. One of the purposes of this paper is to study the human activities that could trigger forest and peatland fires in OKI District. The results of this study are expected to produce information about the causes of fires and provide a scientific based information for policymakers to prevent forest and peatland fires in OKI District. This research was conducted in six villages in three sub-districts, Perigi and Riding Village in Pangkalan Lampam Sub-District; Ulak Depati and Jungkal Village in Pampangan Sub-District; and Pulu Beruang and Ujung Tanjung Village in Tulung Selapan Sub-District. This research method is field observations, interviews, and analyzing Terra/Aqua MODIS satellite imagery data to get the burned area. Based on the interview,it had been found that the main behavior of the community triggers peat fires is sonor, land preparation for plantation, and fishing. Terra/Aqua MODIS image analysis reveals that the area burned in 2015 and 2019, mostly occurred in swamp scrub and open land cover. The knowledge and perceptions of the people in OKI Regency on forest and peatland fire control are classified as moderate (56.7% - 83.3%). Community participation in outreach and training activities can increase people knowledge and perceptions on forest and peatland fire control. Public knowledge has an essential correlation with people's perceptions. Positive public perceptions on efforts to control fires will increase their participation. Community participation at the site level will determine the success of controlling forest and land fires.